EFFECTS OF AGMATINE ON ACOUSTIC STARTLE REFLEX AND AUDITORY SYSTEM IN RATS - Saatci, Ã–zlem; Ã‡evreli, Burcu; Uzbay, Tayfun (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2021)
Background: A polyamine, agmatine, has been proposed as a new neurotransmitter in the brain.Objective: The aim of this study was to evaluate the effects of acute and chronic agmatine treatment on the rat auditory system.Methods: Male Wistar albino rats weighing between 280-330 grams were used. Animals were divided into four groups (n= 8 for each group). Acute and chronic agmatine (160 mg/kg) was administered to rats. Prepulse inhibition (PPI) of the acoustic startle reflex (ASR), distortion product otoacoustic emissions (DPOAEs), auditory brainstem responses (ABR) were evaluated in all groups.Results: Both acute and chronic agmatine treatments also significantly disrupted PPI. Chronic but not acute treatment with agmatine produced some DPOAE and ABR changes in rats.Conclusion: Our results suggested that chronic agmatine treatment for seven days resulted in some significant negative changes in cochlear function. Because the PPI of the ASR is also used as an indicator for psychoses, such as schizophrenia, in human and experimental animal studies, our findings also imply that the DPOAE and ABR tests may also be considered in the diagnosis and follow-up of patients with psychoses.